Efektivitas Games Matematika Edukatif Aplikasi Phet Berbasis Model Problem Based Learning Di Kelas 4 MI Muhammadiyah 2 Kudus - Ningsih, Vina Merliani Vidia; Anggraini, Dian Mustika Anggraini; Safitri, Reny Safitri; Ma’sum, Chandra Ali Ma’sum (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research aims to instill the effectiveness of educational mathematics game media through the PhET application which is based on the Problem Based Learning (PBL) learning model on student learning outcomes in class 4 MI Muhammadiyah 2 Kudus on the topic of fractions. This research uses a quantitative approach with a pre-experimental design using One Group Pretest-Posttest Design. The data analysis process includes normality test, homogeneity test, and paired sample t-test. Research findings indicate that the application of educational mathematics game media through the PBL-based PhET application significantly improves student learning outcomes in fraction material. The average pretest score was 59.06, which increased to 68.44 on the posttest. The normality test shows a significance of 0.314 > 0.005, indicating that the data has a normal distribution. The homogeneity test shows a significance of 0.089 > 0.05, indicating that the data is homogeneous. The results of the paired sample t test show a Sig value, (2-tailed) of 0.010 > 0.05, so the null hypothesis is accepted. Therefore, it can be concluded that the use of educational mathematics game media through the PhET application based on the PBL model has a significant influence on student learning outcomes in class 4 of MI Muhammadiyah 2 Kudus.